2020
DOI: 10.1021/acs.macromol.0c00596
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport in Ampholytic Polymers: The Role of Hydrogen Bonding and Water Uptake

Abstract: The low thermal conductivity of amorphous polymers typically prevents their usage in thermal management applications. Therefore, increasing their intrinsic thermal conductivity poses an exciting scientific challenge. One approach is to promote attractive interchain interactions. Here, we investigate the thermal conductivity of several ampholytic polymers. This unique class of polymers offers H-bond donor and acceptor groups in each repeat unit and constitutes an onecomponent system. We use IR spectroscopy to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…As shown in Figure A, two apparently different peaks at 2993 and 1637 cm –1 attributed to CH and CO stretching vibrations in the aldehyde group were found, which verified the formation of polyglycerol aldehydes. The lower frequency of the CO stretching vibration than those of common ones should be due to the hydrogen bonding …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Figure A, two apparently different peaks at 2993 and 1637 cm –1 attributed to CH and CO stretching vibrations in the aldehyde group were found, which verified the formation of polyglycerol aldehydes. The lower frequency of the CO stretching vibration than those of common ones should be due to the hydrogen bonding …”
Section: Resultsmentioning
confidence: 96%
“…The lower frequency of the CO stretching vibration than those of common ones should be due to the hydrogen bonding. 26 Figure 4B shows the FTIR spectra of native zein, Zein-PG-2, Zein-PG-6, and Zein-PG-10. Typical characteristic peaks of zein were observed, such as the broad and strong peak at 3419 cm −1 assigning to OH stretching vibrations, and peaks at 1650 and 1550 cm −1 corresponding to amide I and II in proteins, which are in accordance with those reported from ref 27.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As previously reported, enhanced intermolecular interactions between the polymer chains and the additives are an advantage for obtaining high thermal conductivity in drawn composite films. , While anisotropic polymer composites with high thermal conductivities have been reported for stretched polyethylene, to date studies of more polar anisotropic polymer composites, like PVA films employing green processes (that is, avoiding organic solvents), have been less prevalent. PVA is an atactic, water-soluble polymer with an orthorhombic unit cell and planar zigzag configuration similar to polyethylene, resulting in dense packing in the crystal lattice with a high theoretical modulus, strength, and thermal conductivity. ,, …”
Section: Introductionmentioning
confidence: 95%
“…As the unit cell volume of YH 3 is compressed, all bond lengths in YH 3 decrease significantly, and the bond energy increases sharply, especially the H-H bonds with weak covalent interactions. For crystalline materials, the enhancement of bond energy will increase the force constant matrix of lattice vibration, which makes the phonon frequency and group velocity increase rapidly (Ouyang and Hu, 2015;Hummel et al, 2020), especially for the acoustic phonon branch. Moreover, the increase of pressure can weaken the phonon-phonon scattering and increase the phonon relaxation time, thus enhancing the material's thermal conductivity (Beldjoudi et al, 2019).…”
Section: Phonon Lifetime and Phase Spacementioning
confidence: 99%
“…Especially the materials with high thermal conductivity and excellent mechanical properties are of great importance in solving the heat dissipation problem of highly integrated electronic devices (Ghosh et al, 2008). Meanwhile, the thermal transport properties of superconductors have also been investigated Tanaka et al, 2017;Hummel et al, 2020). For example, Ito et al (2005) found the thermal conductivity of the yttrium hydrides can reach about 80 W/mK, which is larger than that of metal and depends significantly on temperatures.…”
Section: Introductionmentioning
confidence: 99%